Multi-fractal analysis of the earth’s electromagnetic field time variations caused by the powerful geospace storm occurred on September 7-8, 2017 - Chernogor, L.F.; Garmash, K.P.; Lazorenko, O.V.; Onishchenko, A.A. (Вопросы атомной науки и техники, 2018)
The results of multi-fractal analysis of time variations of the Earth’s electromagnetic field caused by the powerful geospace storm occurred on September 7-8, 2017 were considered. To obtain the most detailed results, the multifractal detrended fluctuation analysis, the Hurst exponent in sliding time domain window and the continuous wavelet transform were simultaneously applied. The set of numerical characteristics, which describe the peculiarities of
the Earth’s electromagnetic field time variations, was estimated. Розглянуто результати мультифрактального аналізу часових варіацій електромагнітного поля Землі, викликаних потужною геомагнітною бурею, що відбулася 7-8 вересня 2017 р. Для отримання найбільш докладних результатів одночасно застосовано мультифрактальний аналіз флуктуацій без тренда, показник Херста,
який обчислюється в ковзаючому вікні в часовій області, та безперервне вейвлет-перетворення. Оцінено
безліч числових характеристик, які описують особливості часових варіацій магнітного поля Землі. Рассмотрены результаты мультифрактального анализа временных вариаций электромагнитного поля
Земли, вызванных мощной геомагнитной бурей, произошедшей 7-8 сентября 2017 г. Для получения наиболее подробных результатов одновременно применены мультифрактальный анализ флуктуаций без тренда,
показатель Херста, вычисляемый в скользящем окне во временной области, и непрерывное вейвлетпреобразование. Оценено множество числовых характеристик, которые описывают особенности временных
вариаций магнитного поля Земли.